Optimum design of bearingless brushless DC motor modeling with dual loop controller using dragonfly optimizers - Qusay S. Kadhim; Mahmood Swadi; Ali Jafer Mahdi; Mohanad Azeez Joodi; Firas Mohammed Tuaimah; Moanes E. Mohammed; Abbas Hafeth Abbas; Mohamed Salem (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
The article presents the optimal modeling of a Bearingless Brushless DC (BBLDC) motor with an enhanced controller, emphasizing a dual-loop control scheme for torque and suspension windings. The design aims to separate electromagnetic torque and radial suspension forces effectively. The proposal's focus consists of two contributions: firstly, the optimal design of the BBLDC motor; secondly, the application of the Dragonfly Algorithm (DA) for the improvement of the motor's control systems, resulting in reduced torque ripple, rapid and precise tracking, and elimination of overshoot. Comparative results illustrate the superior performance of this technique compared to typical Proportional Integral (PI) controllers, exhibiting quicker response times to reach a steady state and enhanced stability.